Pyopericardium with cardiac tamponade caused by pyogenic liver abscess: a case report - Carolin Steffen; Josef Sägmüller; Dominique Schöneburg; Eva Göncz; Martin Möckel; Sascha Ott; Alexander Lavinius Ungur; Benjamin O ’Brien (Journal of Medical Case Reports)
Abstract Introduction Purulent bacterial pericarditis is a potentially fatal disease with mortality rates reaching 100% if left untreated. Case presentation We present the case of a 33-year-old Caucasian male patient who developed cardiac tamponade, most likely caused by a pyogenic liver abscess communicating with the pericardium. Treatment with antibiotics, extended sepsis therapy, and drainage of the abscess led to a full recovery. Conclusion This report describes a rare but potentially fatal differential diagnosis of aortic dissection and serves as a reminder that lives abscesses can manifest unexpectedly. Clinical signs and symptoms of tamponade can be mistaken as sepsis. In this particular case, the combination of a septic abscess and tamponade caused by pyopericardium posed a diagnostic challenge.